Performance art : from futurism to the present - Goldberg, RoseLee, 1947- (Thames & Hudson world of art, 2011)
First published in 1979, the latest edition of this pioneering study in "the World of Art" series surveys a full century of performance, from the Futurist manifesto of 1909 to the second decade of the new millennium. Art historian and gallery curator Rose Lee Goldberg explains how a medium once used only in sporadic outbreaks of artistic dissent has become, over the course of a century, a vital and integral part of the contemporary mainstream and a global phenomenon